2015
DOI: 10.18632/oncotarget.4234
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB, p38 MAPK, ERK1/2, mTOR, STAT3 and increased glycolysis regulate stability of paricalcitol/dexamethasone-generated tolerogenic dendritic cells in the inflammatory environment

Abstract: Tolerogenic dendritic cells (tDCs) may offer an intervention therapy in autoimmune diseases or transplantation. Stable immaturity and tolerogenic function of tDCs after encountering inflammatory environment are prerequisite for positive outcome of immunotherapy. However, the signaling pathways regulating their stable tolerogenic properties are largely unknown. In this study, we demonstrated that human monocyte-derived tDCs established by using paricalcitol (analogue of vitamin D2), dexamethasone and monophosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 40 publications
3
46
2
Order By: Relevance
“…In addition to this potential mechanistic link, STAT‐3 has recently been demonstrated to be a direct transcriptional activator of HK2 . This direct effect of STAT‐3 activation on glycolysis through up‐regulation of HK2 has been described previously in cancer cells, including those of the breast, ovary, and bladder . Similarly, inhibition of STAT‐3 by small interfering RNA significantly decreases HK2 protein, glucose consumption, and lactate production in human hepatocellular carcinoma cells .…”
Section: Discussionmentioning
confidence: 58%
“…In addition to this potential mechanistic link, STAT‐3 has recently been demonstrated to be a direct transcriptional activator of HK2 . This direct effect of STAT‐3 activation on glycolysis through up‐regulation of HK2 has been described previously in cancer cells, including those of the breast, ovary, and bladder . Similarly, inhibition of STAT‐3 by small interfering RNA significantly decreases HK2 protein, glucose consumption, and lactate production in human hepatocellular carcinoma cells .…”
Section: Discussionmentioning
confidence: 58%
“…Besides, activation of several signal pathways was found to be involved in chronic inflammation such as NF-κB (32). Notably, recent studies revealed that activation of NF-κB increased glycolysis in the inflammatory environment (33). In the present study, we integrated the association between IL-8 and glycolysis.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, there are considerable experimental data showing that pre‐treatment of DC with LPS generates cells that promote tolerance rather than immunity15, 26, 27, 28, 29, 30, 31, 32 although the mechanism of tolerance induction in DC is not fully understood. Lipopolysaccharide‐activated macrophages and DC become refractory to further stimulation with LPS,33 a phenomenon known as endotoxin tolerance (ET), which has been attributed to various factors including: (i) the blockade of intracellular signalling events and subsequent gene re‐programming; (ii) up‐regulation of anti‐inflammatory cytokines like interleukin‐10 (IL‐10) and transforming growth factor‐ β (TGF‐ β ); and (iii) down‐regulation of surface expression of the TLR4 receptor 34.…”
Section: Introductionmentioning
confidence: 99%